Nutrition-sensitive Water Management: Guidance for Irrigation Interventions - Chase, Claire (2020)
In the water sector we have an immense responsibility to invest in approaches that will secure food and water security for vulnerable populations in the future. Chronic undernutrition early in life can cause cognitive and physical impairments that prevent children from achieving their full potential and have lasting consequences on the human capital that is essential for economies of the future to be competitive.The World Bank has developed a Water and Nutrition framework to support the inclusion of nutritional considerations in the design of water operations and to help formulate nutrition-enhancing water policy. Alongside this framework we have developed a set of guidance notes that describe the evidence of how water sector investments across irrigation, water management, and water supply and sanitation impact early child nutrition and summarize recommendations on how to design interventions for greater impact. It is often necessary to enhance current approaches to service delivery and water management because these have mainly been designed with more upstream outcomes in mind, such as improvements in access and use for water and sanitation services and improvements in availability of food and income for irrigation investments. It is also necessary to identify ways to coordinate with other sectors to help ensure that children receive all the necessary nutrition inputs that lead to better outcomes, and not just water-related inputs.